Effect of Reheating Schedules on the Hot Working Behavior of Az31 Magnesium Alloy - L. Shang (Canadian Institute of Mining, Metallurgy and Petroleum, 2006)
In conventional continuous hot rolling processes, metals are usually reheated to a temperature such that the workpiece will maintain appropriate hot working characteristics as it proceeds through the rolling mill, assuming that the temperature is continually decreasing. Metallurgically, reheating will reduce micro-segregation in the as-cast material, may increase the as-cast grain size and will affect any second phase particles present in the as-cast structure. All these changes can affect the hot working characteristics, and the final as-hot rolled microstructure. In order to study the effect of reheating on AZ31 magnesium alloy, a plate sample was cast in a water cooled copper mould and a series of compression tests was performed at a temperature of 350 °C, strain rate 0.01 5-1, and strains from 0.2 to 1.0, after different reheating schedules. It was found that there is no significant difference in flow behavior between the as-cast sample and all but one of the reheated ones. The reheat treatment of the 'anomalous' sample was a two stage heat treatment; it was first reheated to 450 °C, cooled to room temperature, then reheated to 350 °C. The effect on the flow curve was to increase the flow stress. This result may be related to changes in second phase particle characteristics.